Marine parasitology - Rohde, Klaus, 1932- (CSIRO ; CABI, 2005)
This comprehensive, authoritative and up-to-date work provides the definitive overview of marine parasites worldwide. It is an invaluable reference for students and researchers in parasitology and marine biology and will also be of interest to ecologists, aquaculturists and invertebrate biologists.